Estetika Jilbab Syar’i: Genealogi Jilbab dan Moderasi Beragama di Indonesia - Nurhayati, Nurhayati (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2023)
Fashion trends that are growing are not only targeting adults but also teenagers and children. In fact, Citayam Fashion Week is a fashion show that is carried out by various groups without age limits at the zebra crossing in the Depok, Citayam, and Bojonggede areas of Jakarta. Technological developments not only affect fashion trends but also affect the culture and mindset of society. Therefore, the development of modern times, followed by developments in information technology, cannot be avoided or even become fanatical towards other people who continue to follow this fashion trend. One of them is the case of a student at SMAN 1 Banguntapan, Yogyakarta, who was forced to wear the headscarf, among other cases. This article uses the descriptive-analytical-thematic method with a type of library research. This article will outline: 1) What is the genealogy of the veil in Indonesia? 2) How is the aesthetics of the syar’i headscarf in interpretation and reality? 3) How are the efforts to moderate religion in Indonesia in the veil verse? One of them is by extending the headscarf over the woman’s head to the chest or covering all the limbs except for the face and palms. This aims to protect oneself from interference by bad men while maintaining honor. If human honor is maintained, there will be no more harassment or acts of violence committed, and efforts to maintain prosperity in human life can be realized.